In Vitro Cultures of Adipose-Derived Stem Cells: An Overview of Methods, Molecular Analyses, and Clinical Applications - Jankowski, Maurycy; Dompe, Claudia; Sibiak, Rafał; Wąsiatycz, Grzegorz; Mozdziak, Paul; Jaśkowski, Jędrzej M; Antosik, Paweł; Kempisty, Bartosz; Dyszkiewicz-Konwińska, Marta (Cells, 2020)
Adipose-derived stem cells (ASCs) exhibiting mesenchymal stem cell (MSC) characteristics, have been extensively studied in recent years. Because they have been shown to differentiate into lineages such as osteogenic, chondrogenic, neurogenic or myogenic, the focus of most of the current research concerns either their potential to replace bone marrow as a readily available and abundant source of MSCs, or to employ them in regenerative and reconstructive medicine. There is close to consensus regarding the methodology used for ASC isolation and culture, whereas a number of molecular analyses implicates them in potential therapies of a number of pathologies. When it comes to clinical application, there is a range of examples of animal trials and clinical studies employing ASCs, further emphasizing the advancement of studies leading to their more widespread use. Nevertheless, in vitro studies will most likely continue to play a significant role in ASC studies, both providing the molecular knowledge of their ex vivo properties and possibly serving as an important step in purification and application of those cells in a clinical setting. Therefore, it is important to consider current methods of ASC isolation, culture, and processing. Furthermore, molecular analyses and cell surface properties of ASCs are essential for animal studies, clinical studies, and therapeutic applications of the MSC properties.
Keywords: buněčná diferenciace; Models, Animal; molecular studies; in vitro; Adipocytes; adipose-derived stem cells; tukové buňky; Cell Culture Techniques; Humans; clinical trials; lidé; modely u zvířat; Cell Differentiation; buněčné kultury